2020
DOI: 10.25134/erjee.v9i1.3778
|View full text |Cite
|
Sign up to set email alerts
|

The roles of critical incidents to construct public senior high school english teachers’ identities development

Abstract: This study investigated the role of critical incidents (CIs) to construct Public Senior High School English teachers’ identities development. The researchers examined the meanings of CIs and how these developed their identities as Public Senior High School English teachers.  To gain the data, the researchers conducted Open-Form Questionnaire and Open-Ended Interview toward eight Public Senior High School English teachers in Yogyakarta. The data were collected using narrative inquiry statements which displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The findings of the current study corroborate the results of the research conducted by Nazari & De Costa (2021), who found that CIs negatively influences teachers' agency and emotions. The results substantiate findings of other studies in which the most recurring CI sources are reported to be learners' unwelcoming behaviors (e.g., Atai & Nejadghanbar, 2016;Karimi & Nazari, 2019;Molani et al, 2021;Pourhassan & Nazari, 2021;Putri & Kuswandono, 2020). In some events reported, the teachers identified the students as problematic, expecting them to act more politely and discreetly.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings of the current study corroborate the results of the research conducted by Nazari & De Costa (2021), who found that CIs negatively influences teachers' agency and emotions. The results substantiate findings of other studies in which the most recurring CI sources are reported to be learners' unwelcoming behaviors (e.g., Atai & Nejadghanbar, 2016;Karimi & Nazari, 2019;Molani et al, 2021;Pourhassan & Nazari, 2021;Putri & Kuswandono, 2020). In some events reported, the teachers identified the students as problematic, expecting them to act more politely and discreetly.…”
Section: Discussionsupporting
confidence: 87%
“…However, students may extrapolate outside feelings unrelated to the teachers' teaching practices. Putri and Kuswandono (2020), in an EFL context, identified the students' misbehavior as a critical incident claimed by the high school Indonesian EFL teachers.…”
Section: Discussionmentioning
confidence: 99%